Data Analysis and Development of Idle Games: Understanding Their Impact on Relaxation and Socialization in Young Adults - Eka Meriyadi; Tony Wibowo; Tony Tan (Jurnal Indonesia Sosial Teknologi, 2024)
This study examines the impact of idle games on relaxation and socialization among young adults using a quantitative approach and the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Idle games, characterized by minimal interaction and gradual progression, have gained popularity due to their potential benefits in alleviating stress and promoting social connectivity. Through a quantitative survey involving respondents aged 18-35, we collected data to test hypotheses regarding the relationship between idle game usage, relaxation levels, and socialization. The analysis results indicate that idle games significantly contribute to relaxation, providing a low-stress environment that allows players to unwind. Additionally, these games facilitate socialization by offering platforms for interaction and community building, thereby strengthening social bonds among players. Using the UTAUT framework, we identified that performance expectancy, effort expectancy, facilitating conditions, and social influence play crucial roles in the acceptance and use of idle games.